FTA analysis of the failure in the horizontal fluidity test - Blaško, Peter; Petrík, Jozef (Metallurgical and Materials Engineering, 2015)
The purpose of the paper was to evaluate the probability of the top event in the fluidity test by Fault Tree Analysis (FTA). One of the important tests used in the foundry practice is the test of the fluidity. Fluidity is the ability of the molten metal to fill the cavity of the molds and create a cast. The AlSi10MgMn (EN 1706) alloy with 5 or 10.54 % of silica was the experimental material. The melted alloy was cast into "horizontal" three-channel mold to test its fluidity. The pouring temperatures were between 605 and 830 °C. In some cases, the experiment was not successful, for a some reasons. This fact led to a waste of time, energy, potential risk of accident, confusion among participants, especially "beginners" founders and became an impulse for the analysis of creation and possible events of fault for the fluidity test using the FTA. It has been found that for the probability of the top event in examined process was disproportionately high (0.29824). The Monte Carlo method was used for the simulation of the effect of decreasing the probability of basic events on the probability of the top event - the fault of the fluidity test.